2008 58th Electronic Components and Technology Conference 2008
DOI: 10.1109/ectc.2008.4550046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and analysis of integrated passive device technologies for wireless radio frequency module

Abstract: We have investigated the existing integrated passive device (IPD) technologies for cost effective IPD solutions for discrete radio frequency (RF) module. Based upon the investigation in terms of cost, size, performance & technology maturity, it comes out that silicon, glass & LTCC are the suitable technologies. We have designed IPDs using these technologies having same foot print to satisfy Intel Wi-MAX specs. Have taped out, validated the samples and made an electrical performance and cost comparison among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Intel Corporation once investigated a silicon-based IPD WiMax module with comparison to a glass-based IPD module and LTCC-based IPD module in terms of cost, size, performance, and technology maturity [10]. It is concluded that the silicon-based IPD technology is a good choice for RF modules.…”
Section: Sop Using Silicon-based Ipdmentioning
confidence: 96%
“…Intel Corporation once investigated a silicon-based IPD WiMax module with comparison to a glass-based IPD module and LTCC-based IPD module in terms of cost, size, performance, and technology maturity [10]. It is concluded that the silicon-based IPD technology is a good choice for RF modules.…”
Section: Sop Using Silicon-based Ipdmentioning
confidence: 96%
“…where is given in (8). Significantly, the interstage matching of cascaded stages can be achieved by designing the GIPD balun, owing to that the proposed bifilar transformer-based GIPD balun has an impedance transformation between primary and secondary windings.…”
Section: Bifilar Transformer-based Gipd Balunmentioning
confidence: 99%
“…This paper proposes a low-noise and high-linearity wideband flip-chip CMOS RFE stacked with glass integrated passive devices (GIPDs). In the past, a number of GIPD designs have been proposed for RFE applications [8]- [10]. In [8], the performance of the bandpass filter and diplexer using GIPD technology was investigated and compared with those using silicon and lowtemperature co-fired ceramic (LTCC) technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [13] used MCM-L technology into the passive elements to ensure that the passive elements had a high-Q. LTCC technology uses vertically stacked multiple metal layers and co-fired in ceramic substrate [14]. The advantage of LTCC is its high degree of vertical integration for several components such as inductors, capacitors, transformers, and baluns with low loss and compact size.…”
mentioning
confidence: 99%